Efeito da fração hexânica de frutos e sementes de Ricinus communis (L.) sobre Spodoptera frugiperda J.E. Smith, 1797 (Lepidoptera: Noctuidae) - Di Domenico, Fabiana (2024)
Spodoptera frugiperda is one of the main pests of corn. One of the alternatives proposed for its control is the implementation of products of botanical origin, such as castor bean extract (Ricinus communis L.). The objective of this study was to verify the effect of the hexane fraction of the crude extract of fruits and seeds of R. communis (FHFSRC) on S. frugiperda under laboratory conditions. The following hypotheses were tested: (i) FHFSRC reduces food consumption and causes mortality of S. frugiperda caterpillars; (ii) FHFSRC causes a reduction in total protein content and inhibition of the activity of SOD and AChE enzymes in S. frugiperda, which contributes to growth inhibition and mortality of caterpillars. For this purpose, two bioassays were performed: (1) determination of the lethal concentration (LC50 and LC90) of FHFSRC; (2) physiological and biochemical effects of FHFSRC on S. frugiperda caterpillars. In both bioassays, the treatments were applied through the ingestion of a contaminated artificial diet. For bioassay 1, the following concentrations of FHFSRC diluted in 90% ethanol were tested: 0.00%, 0.50%, 1.0%, 1.50%, 2.0%, 2.5% and 3.0%. The lethal effect was determined by assessing mortality, which was performed daily for five consecutive days after ingestion of the artificial diet containing the treatments. For bioassay 2, the following treatments were tested: T1: 90% alcohol (control); T2: CL50 of FHFSRC; T3: CL90 of FHFSRC; T4: Commercial product Ravel, based on Cinnamomun verum essential oil; T5: distilled water (control). Twenty-four hours after the diet containing the treatments was provided, the following variables were evaluated: mortality, weight gain, superoxide dismutase (SOD) and acetylcholinesterase (AChE) enzyme activities, and total protein concentration of S. frugiperda. FHFSRC at the lethal concentration CL90, supplied through ingestion in a contaminated artificial diet, showed an insecticidal effect on S. frugiperda caterpillars. FHFSRC (CL90) was able to interfere with the metabolic and biochemical activity of the caterpillars, decreasing the total protein content and increasing the SOD activity, suggesting that FHFSRC toxicity may be associated with oxidative damage. FHFSRC (CL50) caused a reduction in the activity of the AChE enzyme.